Chimeric antigen receptor T-cell therapy for multiple myeloma: a consensus statement from The European Myeloma Network - Moreau, Philippe; Goldschmidt, Hartmut (Haematologica, 2019)
Adoptive cellular therapy using chimeric antigen receptor T-cell (CART) therapy is currently being evaluated in patients with relapsed / refractory multiple myeloma (MM). The majority of CAR-T cell programs now being tested in clinical trials are targeting B-cell maturation antigen. Several recent phase I / II trials show promising preliminary results in patients with MM progressing on proteasome inhibitors, immunomodulatory drugs and monoclonal antibodies targeting CD38. CAR-T cell therapy is a potentially life-threatening strategy that can only be administered in experienced centers. For the moment, CAR-T cell therapy for MM is still experimental, but once this strategy has been approved in relapsed/refractory MM, it will become one of the most important indications for this therapy in Europe and world-wide. This manuscript proposes practical considerations for the use of CAR-T cell therapy in MM, and discusses several important issues for its future development.
Gesehen am 15.01.2020